Utilization of CSR to build organizations’ corporate image in Asia : need for an integrative approach - Pang, Augustine (2020)
Corporate social responsibility (CSR) has been found to be a strong predictor of a favorable corporate image [Gray, 1986. Managing the corporate image: The key to public trust. London: Quorum Books]. Websites have become an essential communication platform [Dawkins, 2004. Corporate responsibility: The communication challenge. Journal of Communication Management, 9(2), 108–119]. This study aims to investigate how CSR can be used in enhancing organizational corporate image. Content analyses of 150 corporate websites of organizations in Asia headquartered in Singapore were conducted, followed by in-depth interviews with public relations (PR) practitioners to examine the motivations behind their CSR engagement. Findings showed that organizations utilized CSR as a means to enhance corporate image via four ways: Engaging in two-way conversations with stakeholders, adopting an inside-out communication approach with employees, recognizing the relevance of other CSR communication channels, and communicating CSR with authenticity. However, some organizations hesitate to use CSR communication to enhance their corporate image because they wanted to avoid being seen as using CSR as a promotional tool.